English Language Proficiency of Senior High School Students - Jomel Balinuyus Manuel (Multidisciplinary Journal for Education, Social and Technological Sciences)
This paper aimed to determine the English language proficiency of senior high school students as input for the language extension program at Gammad National High School. Specifically, it determined the students’ proficiency level on the eight (8) parts of speech; the reading comprehension level along literal, interpretative, evaluative, and integrative; and the reading comprehension level on different genres such as a poem, essay, and short story. A descriptive research design was employed in the study. The fifty-one (51) respondents of Grade 11 senior high school students at Gammad National High School were chosen using the total enumeration technique.  An 82-item proficiency test was used as an instrument in gathering the data. Weighted mean was used in analyzing the data. Results of the study show that among the eight parts of speech, the senior high school students performed well in using adverbs, prepositions, and interjections but found it problematic of using verbs. On reading comprehension, the respondents excelled under literal level across all genres but not on integration and evaluation levels. The study concluded that the respondents are “Proficient User of English” or “High” level in using grammar and reading comprehension. They have mastered the basics of using the English language; however, they need to be exposed more to meaningful activities and varied texts to attain a high level of proficiency.